Test and re-test reliability of optimal stimulation targets and parameters for personalized neuromodulation - Fang, Feng; Cammon, Jared; Li, Rihui; Zhang, Yingchun (Frontiers in Neuroscience, 2023)
Protocols have been proposed to optimize neuromodulation targets and parameters to increase treatment efficacies for different neuropsychiatric diseases. However, no study has investigated the temporal effects of optimal neuromodulation targets and pa-rameters simultaneously via exploring the test-retest reliability of the optimal neuro-modulation protocols. In this study, we employed a publicly available structural and resting-state functional magnetic resonance imaging (fMRI) dataset to investigate the temporal effects of the optimal neuromodulation targets and parameters inferred from our customized neuromodulation protocol and examine the test-retest reliability over scanning time.